High performance workplace systems’ influence on safety attitudes and occupational driver behaviour - Warmerdam, A.; Newnam, S.; Wang, Y.; Sheppard, D.; Griffin, Mark; Stevenson, M. (Elsevier BV, 2018)
© 2018 Elsevier Ltd For organisations employing occupational light vehicle drivers, there are unique challenges to developing a safe working environment. Drawing on role theory, this study elaborates on these challenges within a framework that identifies the role of both workplace management practices and individual attributes. The aim of this paper was to explore the relationship between attitudes and behaviour, and the role of High Performance Workplace Systems (HPWS) in moderating these relationships. The sample consisted of 911 drivers and 161 supervisors from 83 organisations. The results suggest that individual drivers’ safety attitudes had a positive effect on safety behaviour in the work-related driver context, yet their organisation's HPWS has a negative impact on this type of safety behaviour. More importantly, organisation's HPWS appeared to moderate the relationship between safety attitudes and safety behaviour, such that safety attitudes had a stronger effect on safety behaviour when HPWS was low, rather than when HPWS was high. These findings suggest that when there is a lack of guidance through HPWS practices, employees draw on individual attitudes to direct behaviour. A key implication of this research is the need for multi-level interventions, addressing individual attitudes through behavioural modification programs, whilst also incorporating reform at the supervisory and senior management levels.